Does Turnover Intention Matter? Evaluating the Usefulness of Turnover Intention Rate as a Predictor of Actual Turnover Rate. (September 2016) - Cohen, Galia; Blake, Robert S.; Goodman, Doug
Turnover research has traditionally examined intention to turnover rather than actual turnover. Such studies assume that leave intent serves equally well as both a proxy for and predictor of employees' actual turnover behavior. The purpose of this study is to provide an agency-level evaluation of the usefulness of turnover intention as a reliable proxy and predictor of actual turnover across 180 U.S. federal agencies, using hierarchical (stepwise) multiple regression. Our findings suggest that, at the organizational level, turnover intention and actual turnover are distinct concepts, predicted by different sets of variables. Based on these findings, we conclude that public managers tasked with retention might have better foresight concentrating on their agencies' unique demographic characteristics and specific management practices, rather than on their employees' self-reported aggregated turnover intention rate.